Determinants of Accounting Students’ Interest in Public Accounting Careers: The Roles of Financial Rewards, Professional Training, and Recognition - Steffie Grace Angeline Br Ginting; Vinny Stephanie Hidayat (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
This research is driven by the ongoing scarcity of public accountants in Indonesia, despite strong demand in the labor market, which reflects limited student enthusiasm for the profession. This study aims to investigate the relationship between financial compensation, professional development, and professional recognition and career interest in public accounting. Since public accounting plays a significant part in business and finance, it is vital to comprehend the elements that influence accounting students' decision to choose this career path. This study employs a survey-based quantitative methodology. Students from the 2021, 2022, and 2023 intakes of Maranatha Christian University's accounting program make up the population and sample. 110 respondents made up the sample, and the following analysis techniques were applied: linear regression, classical assumption, and instrument testing. In order to investigate the association between the independent variables—financial benefits, professional training, and professional recognition—and the dependent variable—interest in a career as a public accountant—data analysis was done using statistical techniques. The study's findings suggest that career interest in public accounting is significantly influenced by monetary compensation and professional recognition. However, interest in a job as a public accountant is not much influenced by professional training. These results imply that competitive compensation and professional recognition are more critical than training opportunities in attracting future public accountants.